2009
DOI: 10.32398/cjhp.v7isi.2004
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial, Socioeconomic, Behavioral, and Environmental Risk Factors for BMI and Overweight Among 9-to-11-Year Old Children

Abstract: This study explored the risk factors for higher BMI and overweight in 9- to 11-year-old children using the 2007 California Children’s Healthy Eating and Exercise Practices Survey. A total of 741 children completed a two-day food and activity diary. Of these, 299 children participated in the follow-up telephone interview, reporting attitudes and beliefs. Linear regressions identified risk factors related to BMI z-scores; logistic regressions were used for binomial overweight status. Independent variables includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 73 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…No association with adiposity in fully adjusted models. Keihner et al 2009 [ 69 ] Cross USA 299 (47.8%), 9–11 y Media: Physical - TV in bedroom. Social – caregiver limit setting around screen-time Food: Social - Caregiver modelling of energy-dense foods Food and activity diary, FMTS; 4 items; CR and PR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No association with adiposity in fully adjusted models. Keihner et al 2009 [ 69 ] Cross USA 299 (47.8%), 9–11 y Media: Physical - TV in bedroom. Social – caregiver limit setting around screen-time Food: Social - Caregiver modelling of energy-dense foods Food and activity diary, FMTS; 4 items; CR and PR.…”
Section: Resultsmentioning
confidence: 99%
“…A study of children aged 9–11 ( n = 502) reported that those with multiple devices (2–3 or more) in their bedroom had higher body fat percentage than children with no devices in their bedroom [ 29 ]. The remaining studies (8/29; 27.6%) reported null associations between availability of media equipment and child adiposity [ 33 , 42 , 45 , 63 , 64 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations